Immune-related gene expression predicts response to neoadjuvant chemotherapy but not additional benefit from pd-l1 inhibition in women with early triple-negative breast cancer - Sinn, Bruno V.; Loibl, Sibylle; Hanusch, Claus A.; Zahm, Dirk Michael; Sinn, Hans Peter; Untch, Michael; Weber, Karsten; Karn, Thomas; Becker, Clemens; Marme, Frederik; Schmitt, Wolfgang D.; Muller, Volkmar; et al. (Clinical Cancer Research, 2021)
Purpose: We evaluated mRNA signatures to predict response to neoadjuvant PD-L1 inhibition in combination with chemotherapy in early triple-negative breast cancer. Experimental Design: Targeted mRNA sequencing of 2,559 transcripts was performed in formalin-fixed, paraffin-embedded samples from 162 patients of the GeparNuevo trial. We focused on validation of four predefined gene signatures and differential gene expression analyses for new predictive markers. Results: Two signatures [GeparSixto signature (G6-Sig) and IFN signature (IFN-Sig)] were predictive for treatment response in a multivariate model including treatment arm [G6-Sig: OR, 1.558; 95% confidence interval (CI), 1.130–2.182; P ¼ 0.008 and IFN-Sig: OR, 1.695; 95% CI, 1.234–2.376; P ¼ 0.002), while the CYT metric predicted pathologic complete response (pCR) in the durvalumab arm, and the proliferation-associated gene signature in the placebo arm. Expression of PD-L1 mRNA was associated with better response in both arms, indicating that increased levels of PD-L1 are a general predictor of neoadjuvant therapy response. In an exploratory analysis, we identified seven genes that were higher expressed in responders in the durvalumab arm, but not the placebo arm: HLA-A, HLA-B, TAP1, GBP1, CXCL10, STAT1, and CD38. These genes were associated with cellular antigen processing and presentation and IFN signaling. Conclusions: Immune-associated signatures are associated with pCR after chemotherapy, but might be of limited use for the prediction of response to additional immune checkpoint blockade. Gene expressions related to antigen presentation and IFN signaling might be interesting candidates for further evaluation.
CRIS-Team Scopus Importer:2021-05-21